The Impact of Strategic Planning on Patient Satisfaction: a case study - Ali Mohammad Mosadeghrad; Amin Ebneshahidi; Nazanin Abdolmohammadi (Kerman University of Medical Sciences, 2018)
The Impact of Strategic Planning on Patient Satisfaction: a case study   Mosadeghrad Ali Mohammad1*, Ebneshahidi Amin2, Abdolmohammadi Nazanin3 1. Associate Professor, Department of Health Management and Economics, School of Public Health, Health Information Management Research Center, Tehran University of Medical Sciences, Tehran, Iran  2. Ph.D, Department of Anesthesiology, Sadi Hospital, Isfahan, Iran 3. BSc, Sadi Hospital, Isfahan, Iran *Correspondence: Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran Tel: 009821-42933006                                                              Email: mosadeghrad@tums.ac.ir Abstract: Background & Objectives: Patient satisfaction is a key hospital quality and effectiveness indicator. Strategic planning is necessary for hospitals to respond to the rapidly changing internal and external environments, to provide quality services, to maximize revenues and to minimize costs. This study aimed to examine the impact of strategic planning on patient satisfaction in a hospital. Methods: A participatory action research was conducted in a private hospital during the period 2012-2014. Hospital strategic plan was developed and implemented. A goal for enhancing patients' satisfaction was determined in the strategic plan. Structural, procedural and cultural interventions were applied to improve patient satisfaction. Patient satisfaction was measured before and after implementing the strategic plan via a valid and reliable questionnaire. Data was analyzed using the SPSS software. Results: The quality of inpatient services and outpatient services were increased 6% and 8.6% respectively. Accordingly, inpatient satisfaction has increased from 77.4% in 2012 to 83.8% in 2014 (a growth of 8.3%). Out patient satisfaction has increased from 71.6% to 88.8% (a growth of 24%) during the same time period. Outpatients' waiting time has declined by 33%. Improving quality of services and patient satisfaction enhanced inpatients' and outpatients' loyalty by 20% and 87% respectively. Conclusion: Developing an appropriate strategic plan, promoting a collaborative and cooperative culture, empowering employees, expanding organizational resources and implementing the strategic plan appropriately improve patient satisfaction and enhance their loyalty.   Keywords: Strategic planning, Inpatients satisfaction, Outpatients satisfaction, Private hospital, case study, Participatory action research   Citation: Mosadeghrad AM, Ebneshahidi A, Abdolmohammadi N. The Impact of Strategic Planning on Patient Satisfaction: a case study. Journal of Health Based Research 2018; 4(1): 13-29.